P339 A study of environmental risk factors in chronic rhinosinusitis. (20th September 2022) - Singha, S. Krishna; Mona, Henam; Das, Shukla; Gupta, Neelima; Vaid, Lakshmi; Ghosh, Chirashree; Singh, N.P
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objectives: Chronic rhinosinusitis (CRS) is a complex disease that incorporates many different conditions. Our aim is to determine the role of environmental risk factors in chronic rhinosinusitis. Methods: This was a case-control study where forty cases of CRS in the age group of 18-62 years were recruited from the ENT-OPD of UCMS and GTB Hospital, Delhi, a tertiary care hospital, along with 40 age-appropriate healthy controls. Informed and written consent was obtained from all the subjects. Detailed history and examination along with routine blood and radiological investigations were done. Subjective assessment of disease was done using visual analog scales of SNOT 22 questionnaire, environmental questionnaire, and saccharine test. Objective assessment was done using endoscopic grading according to Lund and Kennedy scoring. CT scores were also obtained using Lund and Mackay staging system. Passive air sampling was done by the settle plate method and Anderson six-stage cascade impactor was used for active air sampling. Blood agar and Sabouraud dextrose agar plates were inserted on the six stages of the cascade impactor, which were later incubated at 35°C and 25°C respectively, for 18-24 hours. Bioaerosol concentrations were calculated and MicroScan WalkAway system was used to identify bacterial and fungal growth. The correlation between total bioaerosol concentration and the symptom score was done by spearman's correlation coefficient; a comparison of mean total bioaerosol concentration between the case and control groups was done by Mann-Whitney U-test. Results: The mean total bio-aerosol concentration from active air sampling in the case group was 458.52 CFU/m3 and 437.63 CFU/m3 in control, which was not significant. It was found to be negatively correlated, but not significant with various parameters in case groups like SNOT 22 score, environmental exposure score, saccharine test, smoking, and endoscopic score. A positive but insignificant correlation was found between total bioaerosol concentration and absolute eosinophilic count and CT score. The mean CFU/100 mm3 counted after passive air sampling between case and control group was 34.03 and 30.88 CFU/100mm3 which was not significant. Fungal growths were mostly Aspergillus flavus and A. Niger followed by Cladosporium spp. Conclusion: The fungal burden was high in all the households of the case as well as control groups, although, a significant correlation could not be established. The environmental conditions found in this study were found to be conducive to future risk of exacerbation of preexisting fungal infections for which, indoor air quality needs to be monitored.